2002
DOI: 10.1055/s-2002-34573
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Malformations Associated with the Holt-Oram Syndrome - Report on a Family and Review of the Literature

Abstract: The Holt-Oram syndrome (HOS) is characterized by mild-to-severe congenital cardiac defects and skeletal abnormalities of the upper limb. The most common cardiac disorder is an ostium secundum atrial septal defect (ASD), followed by ventricular septal defect (VSD) and ostium primum ASD. Electrocardiographic abnormalities, such as various degrees of atrioventricular block, have also been reported. In addition, hypoplastic peripheral vessels of the upper limbs have been observed. Here, we will report about a fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…[9] Holt–Oram syndrome features abnormalities of the upper limbs and heart. [10] Mutations in TFAP2B, which encodes a neural crest-derived transcription factor, can cause the abnormalities in Char syndrome, characterized by PDA, facial dysmorphism, and skeletal abnormalities of the hand. [11] CHARGE syndrome (Coloboma of the eye, Heart defects (including PDA), Atresia of the choanae, Retarded growth and development, Genital hypoplasia, and Ear anomalies and/or deafness) is a specific collection of nonrandomly occurring congenital anomalies caused by heterozygous mutation of CHD7 transmitted in an autosomal-dominant manner.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Holt–Oram syndrome features abnormalities of the upper limbs and heart. [10] Mutations in TFAP2B, which encodes a neural crest-derived transcription factor, can cause the abnormalities in Char syndrome, characterized by PDA, facial dysmorphism, and skeletal abnormalities of the hand. [11] CHARGE syndrome (Coloboma of the eye, Heart defects (including PDA), Atresia of the choanae, Retarded growth and development, Genital hypoplasia, and Ear anomalies and/or deafness) is a specific collection of nonrandomly occurring congenital anomalies caused by heterozygous mutation of CHD7 transmitted in an autosomal-dominant manner.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal anomalies typically affect the upper limbs and range from phocomelia to subtle abnormalities of the radial ray, such as a triphalangeal or bifid thumb and radial‐ulnar anomalies. Cardiac anomalies vary from simple atrial or ventricular septal defects to major left heart lesions (hypoplastic left heart syndrome or coarctation of the aorta) and conotruncal defects (tetralogy of Fallot, common arterial trunk, double outlet right ventricle).…”
Section: Discussionmentioning
confidence: 99%
“…3,4,12 Cardiac defects are also characteristic, with atrial septal defects of the ostium secundum type being the most frequently found. 5,13 In a review of the literature involving 189 cases of HOS, single cardiovascular malformations such as atrial and ventricular septal defects were found in 125 patients (66%). However, more complex cardiac defects such as a hypoplastic left heart, total anomalous pulmonary venous return, and truncus arteriosus were reported in an additional 33 patients (17%), suggesting that severe cardiovascular malformations other than septal defects in patients with HOS have been underestimated.…”
Section: Discussionmentioning
confidence: 99%